Analisis Pengaruh Harmonisa Terhadap Losses Transformator 500kVA - Rachmat Sutjipto; Wijaya Kusuma; Kemal Zulfianta (Elposys: Jurnal Sistem Kelistrikan, 2022)
With the non-linear load at the State Polytechnic of Malang, it has an impact on the emergence of harmonics and the appearance of currents in the neutral wire, rising temperatures in conductors and losses in transformers.In this study, several THD analyzes were carried out in accordance with the IEEE 519-1992, including neutral current analysis, losses analysis before and after being affected by harmonics, derating analysis and alternative mitigation methods to reduce these harmonic levels. Based on observational data on 500kVA transformers at UPT PP Polinema, it is known that the highest THDi current is 14.5% and exceeds the IEEE 519-1992 standard (12%). As for the THD voltage, the harmonic is 1.87% and is below the standard (5%). Based on the analysis results, it is known that the value of losses from the neutral current is 0.096 kW. It is also known that the total loss is 1.24kW (the PCu loss is 1.2kW and the PFe loss is 0.04 kW. Based on the SPLN 50 standard in 1997, the total allowable losses are 6.6 kW and 7.84 kW after being affected by harmonics, so the total loss of the measurement results is below the standard. From the analysis, it is also known that the derating will occurs in due to harmonics is 71.6 kVA or 14.32% of the transformer capacity. So to reduce the amount of THD current a mitigation is needed in the form of installing a filter that is used to suppress harmonic currents to meet existing standards.